Professional Education and Training for the Next Decade - Sharott, Peter (Pharmacy Education, 2001)
The Pan Thames Pharmacy Symposium 2001 was held on the 19th and 20th July 2001 at the School of Pharmacy,University of London. The event, jointly and university professional aspects symposium was a co-operative hosted by NHS managed service taking its theme as sectors, of education and training. The main programme addressed the new challenges in vocational undergraduate education to those of formal post—registration training and continuing professional development. The symposium was organised and delivered by a numberof agencies including: London Regional Pharmacy Services; South East (South Coast) Pharmacy EducationTraining; School of Pharmacy,University of London; Department of Pharmacy, King’s College London; School of Pharmacy and Biomolecular Sciences, University of Brighton